HUBUNGAN ADEKUASI HEMODIALISIS DENGAN ALBUMIN SERUM PASIEN CKD YANG MENJALANI HEMODIALISIS - Tola'ba, Yuliana; Yusri, Getrudis; Batara, Tiara Ayu (Universitas Islam Negeri Alauddin Makassar, 2024)
The aim of this study was to determine the relationship between hemodialysis adequacy and serum albumin in CKD undergoing hemodialysis at Stella Maris Hospital Makassar. This research method uses cross-sectional research with 41 respondents who are CKD patients undergoing hemodialysis therapy at Sella Maris Hospital Makassar, aged between 22-79 years, hemodialysis adequacy is calculated using the URR and Kt/V formulas and serum albumin is observed by looking at the results. laboratory examination. Results Measurement of hemodialysis adequacy using the URR formula obtained an average result of 63.29% with a standard deviation of 6.9% and hemodialysis adequacy measurements using the Kt/V formula found an average of 1.18 and a standard deviation of 0.23. The results of the observation of serum albumin obtained an average of 3.65 mg/dl with a standard deviation of 0.38 . The results of the study using the Pearson test analysis using both the URR formula and the Kt/V formula showed that there was a significant relationship between adequacy of hemodialysis and serum albumin, which was positively correlated with moderate strength, which means that the more adequate hemodialysis, the higher the albumin value. To increase the albumin value, nurses need to pay attention to and assess the adequacy of hemodialysis.